The lithic industry of Sima del Elefante (Atapuerca, Burgos, Spain) in the context of Early and Middle Pleistocene technology in Europe. Issue 82 (May 2015) - de Lombera-Hermida, Arturo; Bargalló, Amèlia; Terradillos-Bernal, Marcos; Huguet, Rosa; Vallverdú, Josep; García-Antón, Maria-Dolores; Mosquera, Marina; Ollé, Andreu; Sala, Robert; Carbonell, Eudald; Rodríguez-Álvarez, Xosé-Pedro
Abstract: This paper presents the lithic assemblages documented at Sima del Elefante (TE) and their importance in the context of the Early and Middle Pleistocene human occupation of Europe. We also study changes in human behaviour within the context of the palaeoenvironmental evolution of the Sierra de Atapuerca. This site has characteristics that are of great value for the study of human evolution. The lower levels of TE (Units TE7–TE14) are an essential reference for understanding the early stages of the colonization of Europe. The TE9c level has provided stone tools (Mode 1), faunal remains, and human fossils dated to 1.22 Ma (millions of years ago). Moreover, this is one of the few European sites with a stratigraphic sequence that includes remains of human occupations predating the Jaramillo subchron (Early Pleistocene) and from the Late Middle Pleistocene (Units TE18–TE19). Despite this, the presence of archaeologically sterile units (TE15–17) prevents us from establishing a continuous relationship between the Early and Middle Pleistocene human settlements and, consequently, between their technological and behavioural differences. We can, however compare the technological and palaeoeconomic strategies adopted by different species of hominins during two key phases of the occupation of Europe.